Partner switching and metabolic flux in a model cnidarian–dinoflagellate symbiosis - Matthews, Jennifer L.; Oakley, Clinton A.; Lutz, Adrian; Hillyer, Katie E.; Roessner, Ute; Grossman, Arthur R.; Weis, Virginia M.; Davy, Simon K. (Proceedings of the Royal Society. B, Biological sciences, 2018)
Metabolite exchange is fundamental to the viability of the cnidarian–Symbiodiniaceae symbiosis and survival of coral reefs. Coral holobiont tolerance to environmental change might be achieved through changes in Symbiodiniaceae species composition, but differences in the metabolites supplied by different Symbiodiniaceae species could influence holobiont fitness. Using 13C stable-isotope labelling coupled to gas chromatography–mass spectrometry, we characterized newly fixed carbon fate in the model cnidarian Exaiptasia pallida (Aiptasia) when experimentally colonized with either native Breviolum minutum or non-native Durusdinium trenchii. Relative to anemones containing B. minutum, D. trenchii-colonized hosts exhibited a 4.5-fold reduction in 13C-labelled glucose and reduced abundance and diversity of 13C-labelled carbohydrates and lipogenesis precursors, indicating symbiont species-specific modifications to carbohydrate availability and lipid storage. Mapping carbon fate also revealed significant alterations to host molecular signalling pathways. In particular, D. trenchii-colonized hosts exhibited a 40-fold reduction in 13C-labelled scyllo-inositol, a potential interpartner signalling molecule in symbiosis specificity. 13C-labelling also highlighted differential antioxidant- and ammonium-producing pathway activities, suggesting physiological responses to different symbiont species. Such differences in symbiont metabolite contribution and host utilization may limit the proliferation of stress-driven symbioses; this contributes valuable information towards future scenarios that select in favour of less-competent symbionts in response to environmental change.